The Animal Farm: A Mathematical Model for the Discussion of Social Standards for Control of the Environment - Thomas, Harold A. (Quarterly Journal of Economics, 1963)
Journal Article The Animal Farm: A Mathematical Model for the Discussion of Social Standards for Control of the Environment Get access Harold A. Thomas, Jr. Harold A. Thomas, Jr. Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 77, Issue 1, February 1963, Pages 143–148, https://doi.org/10.2307/1879377 Published: 01 February 1963